Comparing the inactivating efficacy of enteric bacteria in seawater treated with different configurations of continuous flow‐through ultraviolet devices: single‐pass and recirculation. Issue 9 (2nd July 2019) - Romero‐Martínez, Leonardo; Duque‐Sarango, Paola; Acevedo‐Merino, Asunción; Nebot, Enrique
Abstract: BACKGROUND: Industrial and commercial activities may require seawater disinfection for which ultraviolet (UV) irradiation is a widely used technology. Ultraviolet devices are commonly used in laboratory to evaluate the disinfection efficacy, looking for the highest control of the experimental conditions such as collimated beam reactor or continuous flow reactors with recirculation. However, commercial applications usually require the application of the UV treatment by means of one single pass through the reactor. The objective in this article is to evaluate and compare the efficacy achieved by two different continuous flow systems, i.e. single‐pass and recirculation devices, on bacteria in buffered distilled and seawater matrices. RESULTS: Survival data obtained with a single‐pass device followed by disinfection kinetics according to the log‐linear + shoulder model, requiring a dose of 5.87 mJ cm −2 to inactivate one log unit of the initial concentration of the pure strain Escherichia coli ATCC 11229. The survival achieved with a recirculation reactor followed by a biphasic model, required 12.86 mJ cm −2 to inactivate one log unit of the initial concentration and showed loss of efficacy at higher doses. There was substantial loss of the inactivating efficacy in the treatment of bacteria in seawater using the recirculation device. Natural populations of Escherichia coli and Enterococcus sp. were more sensitive to the UV treatment. CONCLUSION: According to the obtained data and their comparison with previous experiments in the literature, the single‐pass prototype is a better approach for determining the inactivating efficacy of UV systems, in comparison with collimated beam and recirculation devices. © 2019 Society of Chemical Industry